Sprint cycling training improves intermittent run performance - Hardaway Chun-Kwan Chan; Weeraya Ka-Yan Ho; Patrick Shu-Hang Yung (Elsevier, 2018)
Background/Objective: The aim of this study was to examine the effect of sprint cycling training on the intermittent run performance, sprinting speed, and change of direction (COD) ability of recreational intermittent sports athletes. Methods: Sixteen participants participated in the study. The experimental group (EG, n = 8) received a total of 12 sessions of sprint cycling training in a 4-week period and the control group (CG, n = 8) received no training. Both EG and CG were instructed to maintain their daily activity during the 4-week period. Each sprint cycling session consisted of 4-7 sets of 30 s all-out sprint cycling. Results: EG significantly improved in Yo Yo Intermittent Recovery Test (13.4% vs 2.4%,p = 0.006, Effect Size (ES): 0.31 vs 0.04), VO2max (7.8% vs −0.2%, p = 0.006, ES: 0.42 vs 0.00), and power output at VO2max (9.8% vs −4.8%, p = 0.002, ES: 0.91 vs 0.32) compared to CG while no significant changes were found in 30 m sprint times and pro-agility times in both EG and CG. Conclusions: Sprint cycling significantly improved intermittent run performance, VO2max and peak power output at VO2max. Sprint cycling training is suitable for intermittent sports athletes but separate speed and COD training should be included.